2015
DOI: 10.1038/srep09550
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic mechanisms contributing to the synchronous improvement of strength and plasticity (SISP) for TWIP copper alloys

Abstract: In this study, the concept of “twinning induced plasticity (TWIP) alloys” is broadened, and the underlying intrinsic microscopic mechanisms of the general TWIP effect are intensively explored. For the first aspect, “TWIP copper alloys” was proposed following the concept of “TWIP steels”, as they share essentially the same strengthening and toughening mechanisms. For the second aspect, three intrinsic features of twinning: i.e. “dynamic development”, “planarity”, as well as “orientation selectivity” were derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The high magnification image and the fast Fourier transformation (FFT) pattern, shown in Fig. 6(b and c), reveal the formation of deformation twins and ε-Co phase at the γ-Co lamellae, which are generated by a strain-induced phase transformation (SIPT)313233. These ε-Co precipitates are located near the deformation twins situated at the γ-Co lamellae.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The high magnification image and the fast Fourier transformation (FFT) pattern, shown in Fig. 6(b and c), reveal the formation of deformation twins and ε-Co phase at the γ-Co lamellae, which are generated by a strain-induced phase transformation (SIPT)313233. These ε-Co precipitates are located near the deformation twins situated at the γ-Co lamellae.…”
Section: Resultsmentioning
confidence: 96%
“…The inverse FFT images clearly display the deformation twins in the γ-Co lamellae. Generally, a strain-induced γ → ε phase transformation is commonly observed for polycrystalline cobalt alloys and γ-Co with low stacking fault energy facilitates twinning upon deformation33. Deformation twins have been also found in the various types of f.c.c.…”
Section: Discussionmentioning
confidence: 99%
“…Under tensile deformation, wavy slip and dislocation cell are prevailing in pure Cu, while planar slip and deformation twinning will be activated in the alloyed Cu with lower SFE 18 , 19 . It has been demonstrated that this kind of DTs induced by quasi-static deformation cannot only improves the strength, but also enhances the plasticity, creating a unique effect of synchronous improvement of strength and plasticity in Cu-Al alloys 26 . The underlying mechanisms responsible for the SISP are well analyzed on the basis of the intrinsic features of DT and its critical role in the plastic deformation 26 .…”
Section: Introductionmentioning
confidence: 99%
“…[1,10] In parallel, recent studies show that the face-centered cubic (FCC) alloys with low stacking fault energy (SFE) draw good balance of strength and ductility. [6,[11][12][13] In FCC materials, it is known that SFE can affect the deformation mechanisms significantly. [14][15][16] When the SFE is high, dislocation slip in the wavy mode dominates the plastic deformation.…”
mentioning
confidence: 99%
“…Though tensile strength and ductility are readily improved in FCC metallic materials with decreasing the SFE, [6,[11][12][13]] the ductility cannot be enhanced monotonically as shown in Figure 1(e). Thus the ductility sensitivity to the SFE and grain size was summarized and shown in Figure 4 in both the fine-grained regime and the coarse-grained regime.…”
mentioning
confidence: 99%